Valorization of Food Waste as Animal Feed: A Step towards Sustainable Food Waste Management and Circular Bioeconomy - Pinku Chandra Nath; Amiya Ojha; Shubhankar Debnath; Minaxi Sharma; Prakash Kumar Nayak; Kandi Sridhar; Baskaran Stephen Inbaraj (Animals, 2023)
The growing population and healthy food demands have led to a rise in food waste generation, causing severe environmental and economic impacts. However, food waste (FW) can be converted into sustainable animal feed, reducing waste disposal and providing an alternative protein source for animals. The utilization of FW as animal feed presents a solution that not only tackles challenges pertaining to FW management and food security but also lessens the demand for the development of traditional feed, which is an endeavour that is both resource and environmentally intensive in nature. Moreover, this approach can also contribute to the circular economy by creating a closed-loop system that reduces the use of natural resources and minimizes environmental pollution. Therefore, this review discusses the characteristics and types of FW, as well as advanced treatment methods that can be used to recycle FW into high-quality animal feed and its limitations, as well as the benefits and drawbacks of using FW as animal feed. Finally, the review concludes that utilization of FW as animal feed can provide a sustainable solution for FW management, food security, preserving resources, reducing environmental impacts, and contributing to the circular bioeconomy.